Pengaruh Promosi Kesehatan terhadap Deteksi Dini Kanker Serviks pada Wanita Pasangan Usia Subur - Niswanah Mustamin (Lembaga Layanan Pendidikan Tinggi (LL-DIKTI) Wilayah IX Sulawesi, 2020)
This study aims to determine the effect of the method using audio visual media (film) and leaflets in early detection of cervical cancer on increasing knowledge, attitudes and actions of women of reproductive age couples (PUS) at Pusksmas Pampang.